2016
DOI: 10.1016/j.trf.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

From Mackworth’s clock to the open road: A literature review on driver vigilance task operationalization

Abstract: Objective: This review aimed to characterize tasks applied in driving research, in terms of instructions/conditions, signal types/rates, and component features in comparison to the classic vigilance literature. Background: Driver state monitoring is facing increased attention with evolving vehicle automation, and real-time assessment of driver vigilance could provide widespread value across various levels (e.g., from monitoring the alertness of manual drivers to verifications of readiness in transitions of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 58 publications
(47 reference statements)
1
15
0
Order By: Relevance
“…This is a pertinent research finding as it adds to the growing body of literature that shows that drivers are at risk of becoming disengaged from the driving task, both for momentary and prolonged periods during automated phases of driving (e.g. Cabrall et al, 2016;Endsley, 2017;Heikoop et al, 2017;Kyriakidis et al, 2017). The role of the driver is likely to shift throughout the duration of a journey between DD, DM and DND .…”
Section: Mode Confusionmentioning
confidence: 85%
“…This is a pertinent research finding as it adds to the growing body of literature that shows that drivers are at risk of becoming disengaged from the driving task, both for momentary and prolonged periods during automated phases of driving (e.g. Cabrall et al, 2016;Endsley, 2017;Heikoop et al, 2017;Kyriakidis et al, 2017). The role of the driver is likely to shift throughout the duration of a journey between DD, DM and DND .…”
Section: Mode Confusionmentioning
confidence: 85%
“…Even if people wanted to supervise driving automation, many decades of human factors research, from Mackworth (1950) to Hancock (2017), suggest risks when humans are tasked to monitor automated processes over extended periods of mostly successful operation. Such risks have been substantiated by recent reviews specific to the driving domain (e.g., Cabrall, Happee, et al, 2016;Gonçalves et al, 2017) and demonstrated in a recent driving simulator experiment (Greenlee et al, 2018).…”
Section: Monitoring Problemsmentioning
confidence: 85%
“…A resounding result from Norman Mackworth (1948) was that despite instruction and motivation to succeed in a sustained attention task (used as an analogy to the critical vigilance of WWII radar operators watching and waiting for enemy target blips on their monitor screens), human detection performance dropped in relation to time-on-task. Thousands of reports have since been published on the challenges of human vigilance, also known as 'sustained attention' (Cabrall, Happee, and De Winter 2016;Craig 1984;Frankmann and Adams 1962). Bainbridge (1983) observed the irony that human supervisory errors are expected when operators are left to supervise an automated process put in place to resolve manual control errors.…”
Section: Solution Area (1): Avoid the Role Of Human Supervision Of Aumentioning
confidence: 99%
“…Compared to other contributing components to vigilance decrements (cf. Cabrall, Happee, and De Winter 2016), the duration of watch period is expected to be an attractive dimension for human-automation interaction system designers due to its intuitive and simplistic operationalisation even despite its potential to interact with other vigilance factors.…”
Section: Solution Area (2): Reduce the Role Along An Objective Dimensionmentioning
confidence: 99%